Characterization of Inhibin from Culture and Non Culture of Granulose Cells for Monoclonal Antibody of Inhibin Production - Amiruddin, Amiruddin; Nizwan Siregar, Tongku; Sutriana, Amalia; Aliza, Dwinna; Armansyah, T. (Jurnal Kedokteran Hewan, 2010)
This study has long-term objectives to obtain immunogenic prototype that can be used to induce multiple ovulation in goats. Working steps of this study were begun with the collection of ovarium from goats, collection of granulose cells, culture of granulose and characterization of molecular weight and isoelectric point (pI) of inhibin protein of granulose cells obtained from culture and non-culture of granulose cells, and followed by preparation of monoclonal antibody toward inhibin. The results showed that inhibin isolated either from culture or non-culture of granulose cells produced a 32 kDa band. Molecular weight of inhibin was measured by Western Blot. The 32 kDa band of SDS PAGE product appeared on Western Blot result was inhibin molecules produced by granulose cells collected fom culture and non-culture of granulose cells that can be identified by Mab-inhibin. Product of IEF gel electrophoresis suggested that inhibin molecule collected from culture of granulose cells has no charge at isoelectric points ranging from 5-6, depends on its total amino acid composition.